Antiproliferative, Ultrastructural, and Physiological Effects of Amiodarone on Promastigote and Amastigote Forms of Leishmania amazonensis. (13th June 2011) - Macedo-Silva, Sara Teixeira de; Oliveira Silva, Thais Larissa Araújo de; Urbina, Julio A.; Souza, Wanderley de; Rodrigues, Juliany Cola Fernandes
Abstract : Amiodarone (AMIO), the most frequently antiarrhythmic drug used for the symptomatic treatment of chronic Chagas' disease patients with cardiac compromise, has recently been shown to have also specific activity against fungi, Trypanosoma cruzi and Leishmania . In this work, we characterized the effects of AMIO on proliferation, mitochondrial physiology, and ultrastructure of Leishmania amazonensis promastigotes and intracellular amastigotes. The IC50 values were 4.21 and 0.46 μ M against promastigotes and intracellular amastigotes, respectively, indicating high selectivity for the clinically relevant stage. We also found that treatment with AMIO leads to a collapse of the mitochondrial membrane potential (Δ Ψ m ) and to an increase in the production of reactive oxygen species, in a dose-dependent manner. Fluorescence microscopy of cells labeled with JC-1, a marker for mitochondrial energization, and transmission electron microscopy confirmed severe alterations of the mitochondrion, including intense swelling and modification of its membranes. Other ultrastructural alterations included (1) presence of numerous lipid-storage bodies, (2) presence of large autophagosomes containing part of the cytoplasm and membrane profiles, sometimes in close association with the mitochondrion and endoplasmic reticulum, and (3) alterations in the chromatin condensation and plasma membrane integrity. Taken together, our results indicate that AMIO is a potent inhibitor of L. amazonensis growth, acting through irreversible alterations in the mitochondrial structure and function, which lead to cell death by necrosis, apoptosis and/or autophagy.